2020
DOI: 10.1111/odi.13590
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA TUG1 participates in LPS‐induced periodontitis by regulating miR‐498/RORA pathway

Abstract: Aim This study was aimed to investigate the role of TUG1 in LPS‐stimulated hPDLCs and to evaluate the potential functions of TUG1 in the pathogenesis of periodontitis. Methods LPS‐stimulated hPDLCs were established as the cell model. CCK‐8 assay was performed to assess cell proliferation ability. Flow cytometry was performed to detect cell cycle distribution, and quantitative RT‐PCR and Western blotting were conducted to measure gene expressions. ELISA kits were used to evaluate the production of inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…Table 3 presents 18 studies that investigated the role of lncRNAs in regulating cellular processes in PDL cells in the presence or absence of stimuli, including studies that compared H-PDL and P-PDL cells [ 60 , 61 , 62 , 63 , 64 , 65 ]. These studies also explored the role of lncRNAs in lipopolysaccharide (LPS)-induced inflammation [ 66 , 67 , 68 , 69 , 70 , 71 ], tumor necrosis factor-alpha (TNF-α)-induced inflammation [ 72 ], mechanical stress [ 73 , 74 , 75 ], hypoxia [ 76 ], and oxidative stress [ 77 ]. To review the outcomes of lncRNA involvement, cell proliferation, apoptosis, inflammatory responses, autophagy, migration, and root resorption were examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 presents 18 studies that investigated the role of lncRNAs in regulating cellular processes in PDL cells in the presence or absence of stimuli, including studies that compared H-PDL and P-PDL cells [ 60 , 61 , 62 , 63 , 64 , 65 ]. These studies also explored the role of lncRNAs in lipopolysaccharide (LPS)-induced inflammation [ 66 , 67 , 68 , 69 , 70 , 71 ], tumor necrosis factor-alpha (TNF-α)-induced inflammation [ 72 ], mechanical stress [ 73 , 74 , 75 ], hypoxia [ 76 ], and oxidative stress [ 77 ]. To review the outcomes of lncRNA involvement, cell proliferation, apoptosis, inflammatory responses, autophagy, migration, and root resorption were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation-stimulating factors released by bacteria, such as LPS and TNF-α, activate the immune response in PDL cells, thereby aggravating the destruction of alveolar bone. Among the 18 studies that investigated the regulatory role of lncRNAs in PDL cells in response to inflammation and other stimuli, 6 studies compared the inflammatory responses of H-PDL and P-PDL cells [ 66 , 67 , 68 , 69 , 70 , 71 ], 7 studies stimulated PDL cells with LPS or/and TNF-α to mimic periodontal inflammation [ 66 , 68 , 69 , 70 , 71 , 72 , 74 ], 3 studies stimulated PDL cells with mechanical stress [ 73 , 74 , 75 ], 1 study subjected PDL cells to hypoxia [ 76 ], and 1 study subjected cells to oxidative stress [ 77 ]. Under these stimuli, the biological activities of PDL cells, including cell proliferation, apoptosis, inflammatory responses, osteogenic differentiation, and autophagy, were explored.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al . reported that TUG1 could decrease the production of inflammatory cytokines to protect against periodontitis via regulating miR‐498/RORA mediated Wnt/beta‐catenin signaling 74 . PTCSC3 could downregulate TLR‐4 to exert anti‐inflammatory effects in periodontitis 57 …”
Section: The Role Of Lncrnas In the Pathophysiology Of Periodontitismentioning
confidence: 99%
“…Previous studies suggested that the roles of miRNAs in periodontitis are regulated by lncRNAs. For example, lncRNA TUG1 mitigates cell injury and cytokine production by regulating miR-498 in LPS-treated PDLCs [ 20 ]. The inhibition effects of miR-20a on secretion of inflammatory cytokines are regulated by MALAT1 in LPS-treated HGF cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%